Analisis Tingkat Konservatisme Akuntansi (Unconditional) Selama Masa Pendemi Covid-19: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2021 - Risa Martasya; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2023)
The research aims to determine whether the uncertainty of the environment caused by the Covid-19 pandemic is driving companies listed on the Indonesia Stock Exchange to implement conservative accounting principles by looking at the differences in unconditional conservatism before and during the Covid-19 pandemic. The population in this study is all companies listed on the Indonesia Stock Exchange from 2018-2021. The sample technique used is purposive sampling, there are 395 companies that are used as research samples for a total of 4 years of observation with a total of 1580 samples. The data used is secondary data obtained from the financial reports of the sample companies for the years 2018 to 2021. The data is obtained from the official website of the Indonesia Stock Exchange (BEI). The data analysis technique used is descriptive analysis, normality test, and hypothesis test using SPSS25 software. Based on the results of the research and the discussions that have been conducted, it can be concluded that the hypothesis is rejected and there is no difference in the level of unconditional conservatism before and during the Covid-19 pandemic.